82.6k views
25 votes
What is the first six terms of the sequence f(n)=(-3)^n​

User Pbearne
by
5.0k points

1 Answer

12 votes

Answer:

The first six terms of the sequence
f\left(n\right)=\left(-3\right)^n are:


-3, 9, -27, 81, -243, 729

Explanation:

Given the sequence


f\left(n\right)=\left(-3\right)^n

Here
n represents any term number in the sequence

Determining the first term

substitute n = 1 in the sequence to determine the first term


f\left(n\right)=\left(-3\right)^n


\:f\left(1\right)=\left(-3\right)^1


f\left(1\right)=-3

Thus, the first term is -3.

Determining the 2nd term

substitute n = 2 in the sequence to determine the 2nd term


f\left(n\right)=\left(-3\right)^n


\:f\left(2\right)=\left(-3\right)^2


\:f\left(2\right)=9

Thus, the 2nd term is 9.

Determining the 3rd term

substitute n = 3 in the sequence to determine the 3rd term


f\left(n\right)=\left(-3\right)^n


f\left(3\right)=\left(-3\right)^3


f\left(3\right)=-27

Thus, the 3rd term is -27.

Determining the 4th term

substitute n = 4 in the sequence to determine the 4th term


f\left(n\right)=\left(-3\right)^n


f\left(4\right)=\left(-3\right)^4


f\left(4\right)=81

Thus, the 4th term is 81.

Determining the 5th term

substitute n = 5 in the sequence to determine the 5th term


f\left(n\right)=\left(-3\right)^n


f\left(5\right)=\left(-3\right)^5


f\left(5\right)=-243

Thus, the 5th term is -243.

Determining the 6th term

substitute n = 6 in the sequence to determine the 6th term


f\left(n\right)=\left(-3\right)^n


f\left(6\right)=\left(-3\right)^6


f\left(6\right)=729

Thus, the 6th term is 729

Therefore, the first six terms of the sequence
f\left(n\right)=\left(-3\right)^n are:


-3, 9, -27, 81, -243, 729

User HalliHax
by
5.7k points